Tłumacz-dokumentalista wobec wyzwań współczesności - Karpińska, Hanna (Slavica Lodziensia, 2019)
The paper shows issues related to the work of Polish-Bulgarian non-literary interpreters. The challenges they face are owing to organizational, work-related and economic reasons. Their number is small and the work they do doesn’t pay well. The influx of new terminology and legal norms makes the need for dictionary and specialized queries ever increasing. The need of training is required (including English language). Also the current state of Bulgarian language lexicography is confronted with user needs and the current state of both languages.